Efek Gel Putih Telur terhadap Penyembuhan Luka Bakar pada Tikus Putih (Rattus novergicus) - Lucia Hendriati; Iwan Sahrial Hamid; Teguh Widodo; Chintya Wandasari; Putu Mirah Risata (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Egg whites traditionally used for the treatment of burns. In this research, egg white was formulated as gel dosage form for easy to use and covered unpleasant odor. The aim of the study was to determined effectivity of egg white in gel dosage form against the healing of superficial partial thickness burns (second degree) on white rats (Rattus novergicus) Wistar strain with parameters were macrophages, fibroblasts, collagen deposit density and wound healing. Research subject were male white rats aged 3 months. Second degree burns on the back of rat with a diameter of 2 cm were made by using a hot coin with temperature 80 ° C for 20 seconds. 18 white rats divided into 3 groups of treatment that is negative control using 0.9% NaCl, positive control using Bioplacenton®, and 40% egg white gel as treatment. Based on the experimental results, white egg gel given topically decreased the number of macrophages and increase the number of fibroblasts, increase the density of collagen deposits and speed up wound healing on second degree burns. White egg gel had significantly difference with negative control of NaCl 0.9% and no significantly difference with Bioplasenton as positive control.